Utveckling av Slitagetålighetstest för Plastdetaljer - Dalal, Ali; Honauer, Ludwig (My University, 2024)
The purpose of the project was to investigate, plan, and, as far as possible, implement a method for evaluating the abrasion resistance of plastic in collaboration with the company FlexLink. Currently, FlexLink uses a method for evaluating abrasion resistance that takes 500–2000 hours to yield results. Our goal was to reduce this time to only 24–72 hours. Specific material choices were not included in the project as the focus was on developing a preliminary method for the materials currently in use. The project began with information gathering and study visits to RISE in Mölndal and Borås for detailed knowledge acquisition on the subject. Subsequently, a selection of methods was made to determine the method with the best potential to meet the objective. The chosen method was the “Pin on Ring” method. This is a modified version of “Pin on Disc,” which is currently used by FlexLink and RISE for material testing. Since the method is based on the existing method, several concept development stages were needed to produce a final product. Finally, CAD models and a rig construction were created to visualize the method. However, implementation could not be completed due to the lack of several critical components needed to build the equipment and thus validate and compare it with the existing method.